Circulating Levels of the Adipokines Monocyte Chemotactic Protein-4 (MCP-4), Macrophage Inflammatory Protein-1β (MIP-1β), and Eotaxin-3 in Severe Obesity and Following Bariatric Surgery - Gentili, A.; Zaibi, M. S.; Alomar, S. Y.; De Vuono, S.; Ricci, M. A.; Alaeddin, A.; Siepi, D.; Boni, M.; Vaudo, G.; Trayhurn, P.; Lupattelli, G. (Hormone and Metabolic Research, 2016)
The aim of the study was to investigate the involvement of the adipokines eotaxin-3, MIP-1β, and MCP-4 in obesity and related comorbidities and the modification of their circulating levels after bariatric surgery. Eighty severely obese subjects and 20 normal-weight controls were included in the study. Circulating levels of MCP-4, MIP-1β, and eotaxin-3, and the main clinical, biochemical, and instrumental parameters for the evaluation of cardiovascular and metabolic profile were determined in controls and in obese subjects at baseline and 10 months after surgery. Within the obese group at baseline, eotaxin-3 levels were higher in males than females and in smokers than non-smokers and showed a positive correlation with LDL-cholesterol, apolipoprotein B, and leptin. MIP-1β showed a positive correlation with age and leptin and a negative correlation with adiponectin and was an independent predictor of increased carotid artery intima-media thickness. MCP-4 levels were higher in obese subjects than controls and showed a positive correlation with body mass index, eotaxin-3, and MIP-1β. Bariatric surgery induced a marked decrease in all the 3 adipokines. MCP-4 is a novel biomarker of severe obesity and could have an indirect role in favoring sub-clinical atherosclerosis in obese patients by influencing the circulating levels of eotaxin-3 and MIP-1β, which are directly related to the main atherosclerosis markers and risk factors. The reduction of circulating levels of MCP-4, eotaxin-3, and MIP-1β could be one of the mechanisms by which bariatric surgery contributes to the reduction of cardiovascular risk in these patients.
Keywords: chemokines; low-grade inflammation; atherosclerosis; laparoscopic sleeve gastrectomy